Analysis of Energy Accumulation and Dispersion Evolution of a Thick Hard Roof and Dynamic Load Response of the Hydraulic Support in a Large Space Stope - Bu, Qingwei; Tu, Min; Zhang, Xiangyang; Zhang, Ming; Zhao, Qingchong (Frontiers in Earth Science, 2022)
Aiming at the mining disaster of thick hard roof, based on the analysis of the mining instability influence of thick hard roof, this paper constructs the mining bearing mechanical model of thick hard roof by using mechanical theory, and obtains the mechanical distribution equation of mining bearing and energy accumulation, mining instability energy release equation and dynamic load response equation of hydraulic support in working face, as well as the dynamic load response characteristics of hydraulic support in working face, put forward the technical countermeasures for strong dynamic pressure control of thick hard roof in working face. The research shows that: (1) the larger the overburden load and suspension span of thick hard roof, the more serious the mining bearing state and energy accumulation evolution; the greater the rock thickness and elastic modulus of thick hard roof, the greater the flexural stiffness of roof, resulting in the increase of roof mining limit breaking span, which indirectly aggravates the mining bearing state and self energy accumulation evolution; (2) the dynamic support resistance of hydraulic support is composed of the dynamic support resistance caused by the release of elastic energy accumulated by mining of thick hard roof, the work done by overlying load, and the static support resistance caused by direct roof gravity; (3) the dynamic support resistance caused by the work of overlying load accounts for the highest proportion, followed by the dynamic support resistance caused by the release of mining elastic energy by thick hard roof; the cause of mining instability and strong dynamic pressure of thick hard roof lies in the large span of mining suspended roof, the large-scale mining suspension structure of thick hard roof leads to high overlying load and large accumulated energy; (4) the mining instability of thick hard roof leads to strong dynamic load response of hydraulic support; adopting pre splitting and roof cutting technology to reduce the breaking span of thick hard roof and reduce the impact dynamic load caused by mining instability of thick hard roof can effectively eliminate the potential safety hazard of over limit bearing of hydraulic support.